The gut microbiota during tamoxifen therapy in patients with breast cancer - Lars E. Hillege; David J. M. Barnett; Janine Ziemons; Romy Aarnoutse; Judith de Vos-Geelen; Robin van Geel; Maaike de Boer; Yvonne E. A. van Riet; Jeroen Vincent; John Penders; Marjolein L. Smidt (Scientific Reports)
Abstract Tamoxifen is essential in treating estrogen receptor-positive (ER+) breast cancer, primarily through its active metabolite, endoxifen. Emerging research suggests potential interactions between tamoxifen and gut microbiota. This study investigates the effects of tamoxifen on gut microbiota composition in postmenopausal ER+ and human epidermal growth factor receptor 2 negative (HER2−) breast cancer patients and explores correlations between gut microbiota and endoxifen plasma levels. This prospective observational study included postmenopausal ER+/HER2− breast cancer patients. Fecal and blood samples were collected before and during 6–12 weeks of tamoxifen therapy. Gut microbiota composition was analyzed using 16S rRNA amplicon sequencing of the hypervariable V4 gene region, and plasma endoxifen levels were measured using liquid chromatography-mass spectrometry. Changes in microbial diversity and composition were assessed, with correlations to endoxifen levels. A total of 62 patients were included. Tamoxifen significantly increased microbial richness (p = 0.019), although overall community structure remained consistent between pre- and during-treatment samples. Notable changes were observed in specific microbial taxa, with significant increases in genera such as Blautia (p adjusted  = 0.003) and Streptococcus (p adjusted  = 0.010), and decreases in Prevotella_9 (p adjusted  = 0.006). No significant correlations between gut microbiota and endoxifen levels were identified after multiple comparisons. Tamoxifen therapy increases gut microbial diversity in postmenopausal ER+/HER2− breast cancer patients, though overall microbial community structure remains stable. The absence of significant correlations with endoxifen levels suggests that while tamoxifen affects the gut microbiota, its role in endoxifen metabolism requires further study. More comprehensive research is needed to understand the relationship between tamoxifen, gut microbiota, and therapeutic outcomes.